Implementation of target cost management (TCM) and its key enablers: A case study of an automotive company / Norhafiza Baharudin - Norhafiza , Baharudin (2016)
Studies show that many established Japanese companies use Target Cost Management (TCM) as a profit planning management tool and a competitive tool for pricing their prod-ucts. Despite the proven benefits of TCM as a key competitive tool, studies also show that many companies, especially in developing countries, still lag behind in the implementation of TCM. Furthermore, even if implemented, TCM practices outside of Japan are a standalone process and the fundamental characteristics of TCM practices in these compa-nies are not the same as in the Japanese companies. Nevertheless, due to the lack of studies on TCM outside of Japan, there is still a lack of understanding concerning how different are the TCM practices compared to the Japanese TCM theoretical model, why the differences occur, and what enablers positively associated with TCM practices in non-Japanese envi-ronment. By using the contingency theory and dynamic capabilities theory as underpinning theories, this study attempts to examine in-depth how different are the TCM practices in non-Japanese environment compared to the Japanese theoretical model, to identify the causes of differences and to determine what enablers have a positive association with the successful implementation of TCM. The research was carried out at Company A, a Malay-sian-Japanese joint venture automotive company. It used the single embedded case study method of K. Yin (2003) with multiple sources of data collection by using qualitative and quantitative approach. Based on previous TCM case studies conducted at Japanese automotive companies, a conceptual framework was developed as the case study guidelines. As for TCM enablers that have a positive association with the successful implementation of TCM, a theoretical framework was developed to find the statistical relationships. The findings showed that the basic fundamental concept of TCM in the case company was similar to the practices in Japanese automotive companies. Nevertheless, the case company coordinated and reconfigured its resources to adapt to the contextual constraints, which caused some differences in the TCM practices. Among nine proposed enablers, only top management support and commitment, training and teamwork were regarded as the key enablers that positively associated with the successful implementation of TCM. This research strength-ens the body of knowledge relating to TCM practices in non-Japanese context particularly in terms of in-depth understanding on TCM practice at Malaysia, how TCM practice was adjusted to fit the contextual constraints, and the critical enablers that support the TCM im-plementation in Malaysia automotive industry context.